A comparative study of Academic Resilience, Academic Self-Efficacy and Social Skills in Students with Divorced and Normal Parents - Zahra Sahraeean; Seyed AbdolHadi Samavi (Iranian Evolutionary Educational Psychology Journal, 2022)
The effect of family background on children's behaviors and emotions has been confirmed in various studies. One of the negative experiences affecting the development of adolescents is divorce of parents. The current study aimed to compare academic resilience, academic self-efficacy and social skills in students with divorced and normal parents in Bandar Lengeh city (Iran). Participants were 108 students (62 students with normal parents and 46 students with divorced parents) who selected by purposive sampling method. Academic Resilience Questionnaire (Samuels, 2004), College Academic Self-Efficacy Scale (Owen & Froman, 1988)  and Teenage inventory of social skills (Inderbitzen & Foster) were used for collecting data. The data was analyzed using the multivariate analysis of variance test (MANOVA). The results indicated there is a significant difference between students with divorced and normal parents in resilience (P<0.05), self-efficacy (P<0.05) and social skills (P<0.05). According the results, students with normal parents had higher scores in the dependent variables. The findings have beneficial implications for psychologists and counselors active in the field of child and adolescent counseling, especially in divorced families.